2010
DOI: 10.3109/15622970902995604
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive function in short- and long-term substitution treatment: Are there differences?

Abstract: Cognitive impairment in drug-dependent patients receiving methadone maintenance treatment has been reported previously, although the literature is limited and results remain controversial. Long-term effects under stable methadone maintenance treatment (MMT) and the possibility of improvement in cognitive performance during long-term substitution treatment have rarely been investigated. We performed a comparative study investigating differences in cognitive functions under short- and long-term methadone treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 32 publications
1
9
0
Order By: Relevance
“…Studies on cognitive function of MMT patients usually describe them as suffering from cognitive impairment as reflected by their poor performance on diverse cognitive tasks 3 5 . Although some investigators have suggested that methadone itself might relate to their impairment, others also reported possible improvement in their cognitive abilities during MMT 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…Studies on cognitive function of MMT patients usually describe them as suffering from cognitive impairment as reflected by their poor performance on diverse cognitive tasks 3 5 . Although some investigators have suggested that methadone itself might relate to their impairment, others also reported possible improvement in their cognitive abilities during MMT 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“…In their review, Højsted et al () concluded that opioid treatment induced no effect or worsening of CF in cancer pain patients and had no effect or improvement in chronic non‐cancer pain patients. Soyka, Zingg, Koller, and Hennig‐Fast () performed a cross‐sectional study investigating opioid substitution treatment and showed that patients receiving long‐term methadone maintenance treatment (MMT; >6 months) had better performances in executive functions and visuo‐construction than patients receiving short‐term MMT. However, Wang, Wouldes, and Russell () showed that MMT is associated with cognitive impairment if the daily dose is higher than 60 mg. One cohort study performed by Dublin et al () assessed the association between opioid use and dementia.…”
Section: Resultsmentioning
confidence: 99%
“…As such, patients with privileges need to manifest at least a minimum level of cognitive performance suitable to fulfi l these responsibilities. Most of the many studies on the cognitive status of MMT patients, however, suggest that it is usually poor (Darke et al 2012;Marvel et al 2012; for see review Wang et al 2013), and only a few studies reported that improvement may occur during treatment (Soyka et al 2010;Bracken et al 2012).…”
Section: Study Samplementioning
confidence: 98%